Method for preparing quantum dot nano material by using biological template and biomimetic synthesis method
Through biological templates and bionic synthesis methods, using polypeptide molecules self-assembly and metal ions to prepare quantum dot nanomaterials with environmentally friendly, high biocompatibility and low cost, solving the problems of high temperature and high pressure and precise control in traditional methods. It has achieved precise regulation of the morphology and structure of quantum dots, and expanded its application prospects in the fields of biomedical and environmental protection.
Patent Information
- Application Number
- CN202411278372.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
The synthesis method of traditional quantum dot nanomaterials has the limitations of high temperature and high pressure requirements and precise control of reaction conditions. Although biosynthesis is environmentally friendly, it is difficult to achieve precise regulation of quantum dot morphology and structure.
Biotemplates and biomimetic synthesis methods are used to form nanostructures through self-assembly of polypeptide molecules, adsorb and bind metal ions, and then add reducing agents and sulfide solutions to prepare quantum dot nanomaterials to achieve precise regulation of quantum dot composite materials.
It has achieved environmentally friendly, high biocompatibility, low-cost quantum dot nanomaterial preparation, with better morphology and structural regulation capabilities, and is suitable for biomedical, environmental protection and nanomaterial fields.
Smart Images

Figure CN119144320A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano composite materials, and in particular to a method for preparing quantum dot nano materials by utilizing biological templates and bionic synthesis methods. Background Art
[0002] Quantum dot nanomaterials are a type of nanoparticle material with a special electronic structure and quantum effect. They are usually composed of tens to hundreds of atoms and are at the nanometer level in size. Therefore, quantum dot nanomaterials have unique optoelectronic properties and electronic properties. Therefore, quantum dot nanomaterials have a wide range of applications in optoelectronic devices, solar cells, bioimaging, quantum dot sensors, quantum computing and communications, environmental monitoring, food safety, etc.; in addition, quantum dots can also be used as nanomaterial enhancers to improve the optical, electrical and mechanical properties of materials, such as for the preparation of high-performance nanocatalytic materials and nanoantibacterial materials.
[0003] Traditional methods for synthesizing quantum dot materials include solvothermal method, thermal decomposition method, microwave synthesis method, gas phase synthesis method, microemulsion method, etc. However, these traditional quantum dot synthesis methods usually have certain limitations; for example, some methods require high temperature and high pressure synthesis conditions to decompose organic precursor compounds, generate metal atoms and then recrystallize into quantum dots; or require precise control of reaction conditions and reaction processes to achieve precise control of quantum dot size and morphology; a milder synthesis method is biosynthesis, that is, using organisms such as microorganisms, plants or animals in organisms to synthesize quantum dots. This method usually has the advantages of environmental friendliness, low cost and biocompatibility, which can promote the application of quantum dot materials in antibacterial, biosensing, environmental monitoring and other aspects. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems and to design a method for preparing quantum dot nanomaterials using biological templates and bionic synthesis methods.
[0005] The present invention provides a method for preparing quantum dot nanomaterials by using biological templates and biomimetic synthesis methods. The method for preparing quantum dot nanomaterials by using biological templates and biomimetic synthesis methods comprises the following steps:
[0006] Step a, synthesis of self-assembling polypeptide nanostructures: by customizing the amino acid sequence of polypeptide molecules and regulating the molecular self-assembly reaction conditions, a self-assembling polypeptide nanostructure is synthesized;
[0007] Step b, adsorption and binding of precursor metal ions: by adjusting the pH value of the self-assembled polypeptide nanostructure solution synthesized in step a, and then adding precursor metal ions, the precursor metal ions are adsorbed and electrostatically bound to the polypeptide nanostructure to form a polypeptide nanostructure / metal ion hybrid;
[0008] Step c, biomimetic synthesis of polypeptide / quantum dot composite nanomaterials: adding a reducing agent and a sulfide solution to the polypeptide nanostructure / metal ion hybrid solution synthesized in step b to prepare polypeptide / quantum dot composite nanomaterials.
[0009] Optionally, in a first implementation of the present invention, step a specifically includes the following steps:
[0010] Step a1, weigh 5-10 mg of polypeptide sample powder in a small beaker, dissolve it in 10 mL of 0.1% trifluoroacetic acid solution under stirring to prepare a polypeptide solution with a concentration of 0.5-1 mg / mL;
[0011] Step a2, reacting the polypeptide solution obtained in step a1 in a water bath at 37-57° C. for 1-3 days to synthesize a self-assembled polypeptide nanostructure, wherein the self-assembled polypeptide nanostructure comprises at least one-dimensional nanofibers and two-dimensional nanosheets.
[0012] Optionally, in a second implementation of the present invention, step b specifically includes the following steps:
[0013] Step b1, taking 5 mL of the self-assembling polypeptide nanostructure solution synthesized in step a, adding 5 mL of the metal ion precursor solution under stirring at a speed of 200 rpm, adjusting the pH value, and reacting at room temperature for 4-6 hours;
[0014] Step b2: the prepared reactants are separated by dialysis bags for standby use, wherein the molecular weight of the dialysis bags is 3000-10000.
[0015] Optionally, in a third implementation of the present invention, the precursor metal ions in step b are chloroaurate ions, silver ions or copper ions.
[0016] Optionally, in a fourth implementation of the present invention, the pH value of the self-assembling polypeptide nanostructure solution in step b is adjusted according to the isoelectric point of the polypeptide.
[0017] Optionally, in a fifth implementation of the present invention, step c specifically includes the following steps:
[0018] Step c1, dissolving the polypeptide / metal ion product separated by dialysis in step b in 2 mL of water, and adding a reducing agent under stirring at a speed of 200 rpm to synthesize metal quantum dots;
[0019] Step c2, dissolving the polypeptide / metal ion product separated by dialysis in step b in 2 mL of water, and adding the sulfide solution under stirring at a speed of 200 rpm to synthesize metal sulfide quantum dots;
[0020] Step c3: removing the unreacted reducing agent and sulfide by centrifugation to synthesize the polypeptide / quantum dot composite nanomaterial.
[0021] Optionally, in a sixth implementation of the present invention, the reducing agent in step c1 is sodium borohydride, and the sulfide in step c2 is sodium sulfide.
[0022] Optionally, in a seventh implementation of the present invention, the centrifugal speed of the centrifugal operation in step c3 is 10,000 rpm and the centrifugal time is 15 min.
[0023] Compared with the existing known technology, the technical solution provided by the present invention has the following beneficial effects:
[0024] 1. The technology described in the present invention customizes the amino acid sequence of polypeptide molecules, utilizes the solution self-assembly method to synthesize polypeptide nanofibers and nanosheets, and uses this as a biological template to prepare quantum dot composite nanomaterials through a biomimetic synthesis strategy.
[0025] 2. The technology described in the present invention introduces self-assembling polypeptide nanomaterials and uses biological molecules as the starting point for synthesis, which has the advantages of being environmentally friendly, highly biocompatible, capable of in-situ synthesis, and low cost;
[0026] 3. The polypeptide molecules used in the technology described in the present invention have more active sites and can better regulate the morphology and structure of quantum dots;
[0027] 4. The technical synthesis process described in the present invention is simple and highly controllable, and can achieve precise regulation of quantum dot composite materials;
[0028] 5. The quantum dot nanocomposite materials synthesized by the technology described in the present invention have broad application prospects in the fields of biomedicine, environmental protection and nanomaterials. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the following detailed description of the preferred embodiment.The drawings are only for the purpose of illustrating the preferred embodiments and are not to be construed as limiting the invention.
[0030] Figure 1 Atomic force microscopy images of self-assembled polypeptide nanofibers;
[0031] Figure 2 This is a transmission electron microscope image of the polypeptide nanofiber / gold quantum dot composite material;
[0032] Figure 3 Atomic force microscopy images of self-assembled peptide nanosheets;
[0033] Figure 4This is a transmission electron microscope image of the polypeptide nanosheet / silver sulfide quantum dot composite material. DETAILED DESCRIPTION
[0034] The present invention is further described below in conjunction with specific embodiments.
[0035] The technical solutions in the embodiments of the present invention are clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0036] In the description of the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0037] In the present invention, the main experimental equipment includes:
[0038] pH meter: An instrument used to measure the acidity and alkalinity of a solution. It can provide very accurate pH readings, which is essential for controlling the environmental conditions of a peptide solution. Different pH values can affect the charge state, solubility, and stability of the peptide. When preparing a peptide solution, a pH meter can ensure that the solution is at the most suitable pH conditions to maintain the optimal activity and structural state of the peptide.
[0039] Heating plate / water bath: used to provide stable temperature conditions, they can precisely control the speed and temperature of heating; temperature is a key parameter in the process of peptide self-assembly. The appropriate temperature can help the peptide form the desired structure, and the heating plate or water bath can ensure that the whole process is carried out at a constant temperature;
[0040] Magnetic stirrer: The magnetic stirrer rotates at the bottom to achieve uniform mixing of the solution. It can effectively promote the dispersion of the components in the solution and can also help control the reaction rate. During the preparation process, the magnetic stirrer helps ensure that all components are evenly dispersed and prevent structural inhomogeneity caused by local concentration differences;
[0041] FM-Nanoview6800 atomic force microscope (Suzhou Feishiman Precision Instrument Co., Ltd.): A high-resolution microscopy technique used to observe the microstructure of the sample surface. It can provide a three-dimensional image of the sample surface at the nanoscale. The use of atomic force microscopy can observe the nanostructures formed by the self-assembly of polypeptides, such as fibrous structures, films, particles, etc.
[0042] Tecnai G2 F20 transmission electron microscope (FEI Company, USA): A high-resolution microscopy technique used to observe the internal structure and morphology of a sample. It generates images by passing an electron beam through an ultra-thin sample; a transmission electron microscope can provide detailed morphological and dimensional information of the sample.
[0043] The polypeptide solid powder used in the examples of the present invention was purchased from Nanjing Jiepeptide Biotechnology Co., Ltd.
[0044] Example 1
[0045] The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods described in this embodiment includes the following steps:
[0046] Step a, synthesis of self-assembling polypeptide nanostructures: by customizing the amino acid sequence of polypeptide molecules and regulating the molecular self-assembly reaction conditions, a self-assembling polypeptide nanostructure is synthesized;
[0047] In this embodiment, 5-10 mg of polypeptide sample powder is weighed in a small beaker and dissolved in 10 mL of 0.1% trifluoroacetic acid solution under stirring to prepare a polypeptide solution with a concentration of 0.5-1 mg / mL; the obtained polypeptide solution is reacted in a 37-57° C. water bath for 1-3 days to synthesize a self-assembled polypeptide nanostructure, wherein the self-assembled polypeptide nanostructure includes at least one-dimensional nanofibers and two-dimensional nanosheets.
[0048] Step b, adsorption and binding of precursor metal ions: by adjusting the pH value of the self-assembled polypeptide nanostructure solution synthesized in step a, and then adding precursor metal ions, the precursor metal ions are adsorbed and electrostatically bound to the polypeptide nanostructure to form a polypeptide nanostructure / metal ion hybrid;
[0049] In this embodiment, 5 mL of the self-assembling polypeptide nanostructure solution synthesized in step a was taken, 5 mL of the metal ion precursor solution was added under stirring at a speed of 200 rpm, the pH value was adjusted (adjusted according to the isoelectric point of the polypeptide), and the reaction was carried out at room temperature for 4-6 hours; the prepared reactants were separated by dialysis bags and set aside, wherein the molecular weight of the dialysis bags was 3000-10000.
[0050] Step c, biomimetic synthesis of polypeptide / quantum dot composite nanomaterials: adding a reducing agent and a sulfide solution to the polypeptide nanostructure / metal ion hybrid solution synthesized in step b to prepare polypeptide / quantum dot composite nanomaterials.
[0051] In this embodiment, the polypeptide / metal ion product separated by dialysis in step b is dissolved in 2 mL of water, and a reducing agent (sodium borohydride) is added under stirring conditions at a speed of 200 rpm to synthesize metal quantum dots; the polypeptide / metal ion product separated by dialysis in step b is dissolved in 2 mL of water, and a sulfide solution (sodium sulfide) is added under stirring conditions at a speed of 200 rpm to synthesize metal sulfide quantum dots; the unreacted reducing agent and sulfide are removed by centrifugation (centrifugal speed of 10000 rpm, centrifugal time of 15 min), and the polypeptide / quantum dot composite nanomaterial is synthesized.
[0052] In this embodiment, sodium borohydride is a strong reducing agent, which is commonly used to reduce metal ions into metal nanoparticles. The stirring speed is set to 200 rpm on the magnetic stirrer to ensure that the solution is evenly mixed. Under continuous stirring, sodium borohydride is slowly added to the polypeptide / metal ion complex solution. As sodium borohydride is added, the color of the solution changes, which is because the metal ions are reduced into metal nanoparticles.
[0053] Example 2
[0054] The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods described in this embodiment includes the following steps:
[0055] Step a, weigh 2 mg of a polypeptide solid powder with a purity of 95% in a beaker, dissolve it in 2 mL of 0.1% trifluoroacetic acid under stirring to form a uniformly dispersed polypeptide solution; then mix the polypeptide solution with trifluoroethanol and dilute it to 0.2 mg / mL, and finally dilute it with ethanol to 0.1 mg / mL to form a polypeptide reaction solution; place the polypeptide reaction solution in a 37°C water bath for 5 days to form polypeptide nanofibers for standby use;
[0056] In this embodiment, the polypeptide sequence of the polypeptide solid powder is lysine-isoleucine-isoleucine-isoleucine-isoleucine-lysine-tyrosine-tryptophan-tyrosine-alanine-phenylalanine. In this sequence, five consecutive isoleucines and two lysines make the polypeptide have a certain hydrophobicity and positive charge, which helps to interact with negatively charged molecules. The presence of tyrosine and tryptophan increases the polarity of the polypeptide, and tryptophan also confers fluorescent properties. Alanine helps to maintain the stable structure of the protein, and the phenylalanine after the alanine increases the hydrophobicity. The terminal phenylalanine enhances the hydrophobicity of the polypeptide and may help to interact with other proteins or cell membrane components.
[0057] In this embodiment, sample preparation: take an appropriate amount of the polypeptide nanofiber solution obtained in step a, drop it onto a clean silicon wafer, ensure that the sample evenly covers the surface of the silicon wafer, let the sample dry naturally or blow dry with nitrogen to remove the solvent and form a stable sample layer;
[0058] Sample loading: Fix the silicon wafer with the sample on the sample stage of the atomic force microscope;
[0059] Atomic force microscope settings: Set the atomic force microscope working mode to non-contact mode or tapping mode, and adjust the scanning parameters;
[0060] Image acquisition: Start atomic force microscope scanning to obtain the three-dimensional morphology image of polypeptide nanofibers;
[0061] Data analysis: The obtained images were analyzed using the software supporting the atomic force microscope to measure the size, diameter and other parameters of the polypeptide nanofibers;
[0062] Results: Figure 1 As shown in the figure, the scanning electron microscope (SEM) image of the polypeptide nanofibers synthesized under the experimental conditions can be seen that these polypeptide nanofibers present an elongated strip structure with a length of 1-2 μm and a diameter of 3-9 nm (average 6 nm). These fibers appear as elongated strip structures in the image, forming a sharp contrast with the surrounding background. This morphology indicates that polypeptide molecules can self-assemble to form an ordered nanostructure under specific conditions.
[0063] Step b, mixing the polypeptide nanofibers obtained in step a with 0.5 mL of 10 mM chloroauric acid, reacting under magnetic stirring conditions (speed 200 rpm) for 12 hours, and then separating by dialysis (molecular weight 3000);
[0064] In this embodiment, dialysis separation is used to separate and purify the product of the reaction between polypeptide nanofibers and chloroauric acid. Dialysis is a separation technology based on molecular size differences, which separates small molecules from large molecules through a semipermeable membrane. In this experiment, a dialysis bag with a molecular weight of 3000 is used. This dialysis bag allows molecules with a molecular weight less than 3000 to pass through, while preventing molecules with a molecular weight greater than 3000 from passing through. In this experiment, the molecular weight of the peptide nanofibers is usually greater than 3000, while the molecular weight of chloroauric acid is smaller, so this dialysis bag can be used; the reaction mixture is placed in the dialysis bag, and the opening of the dialysis bag is sealed tightly to prevent leakage of the mixture; the dialysis bag containing the mixture is placed in a container filled with a large amount of water or other appropriate solvents, and the small molecules in the dialysis bag (such as chloroauric acid) will diffuse into the solvent in the container through the semipermeable membrane, while the peptide nanofibers are retained in the dialysis bag; in order to improve the dialysis efficiency, it is usually necessary to regularly replace the solvent in the container; this can keep the concentration of small molecules in the solvent low, thereby promoting the dialysis process; the dialysis process usually takes several hours to several days, depending on factors such as the molecular weight cutoff value of the dialysis bag, the surface area of the dialysis bag, the volume of the solvent, and the temperature. In this experiment, the dialysis time was 12 hours; after the dialysis is completed, the peptide nanofibers are collected from the dialysis bag. These peptide nanofibers have been reacted with chloroauric acid, and unreacted chloroauric acid and other small molecule impurities have been removed by dialysis; through this dialysis step, the product of the reaction between the peptide nanofibers and chloroauric acid can be effectively separated and purified, providing pure samples for subsequent analysis and application.
[0065] Step c, dilute with water to 2 mL, then add 10 μL of sodium borohydride solution for reduction to synthesize the polypeptide fiber / gold quantum dot composite material, and finally centrifuge the obtained mixed solution (centrifugal speed is 1-000 rpm, centrifugal time is 15 min) and wash 3 times, collect the final precipitate, and disperse it in 2 mL of ultrapure water.
[0066] In this embodiment, the detection process:
[0067] Sample preparation: Take an appropriate amount of the polypeptide nanofiber / gold quantum dot composite material solution obtained in step c, drop it onto the copper mesh, let the sample dry naturally or use filter paper to absorb excess liquid, and ensure that a thin layer of composite material is formed on the copper mesh;
[0068] Sample loading: The copper grid with the sample was fixed on the sample holder of the transmission electron microscope;
[0069] Transmission electron microscope settings: Adjust the operating voltage of the transmission electron microscope to 100-300 kV to obtain a clear image and adjust the appropriate magnification;
[0070] Image acquisition: Start transmission electron microscope scanning to obtain a two-dimensional projection image of the polypeptide nanofiber / gold quantum dot composite material;
[0071] Data analysis: Use the transmission electron microscope software to analyze the obtained images, measure the size, distribution and other parameters of the quantum dots, analyze the selected area electron diffraction (SAED) pattern, and confirm the crystal structure of the quantum dots;
[0072] Results: Figure 2 As shown, the microstructure of the polypeptide nanosheet / silver sulfide quantum dot composite material is shown. It can be seen from the figure that the silver sulfide quantum dots are evenly distributed on the polypeptide nanosheet to form the microstructure of the composite material. These silver sulfide quantum dots appear as dark granules, while the polypeptide nanosheet appears as a lighter background. The silver sulfide quantum dots are very evenly distributed on the polypeptide nanosheet, which indicates that the combination of polypeptide and silver sulfide quantum dots during the synthesis process is effective, and there is no obvious aggregation phenomenon. This uniformly distributed structure is of great significance for the performance and application of the composite material, because uneven distribution may lead to inconsistent material performance. The size of the silver sulfide quantum dots is small and presents a spherical or nearly spherical shape. The size of these quantum dots is within the nanoscale range, which meets the definition of quantum dots. The thickness and morphology of the polypeptide nanosheet are also clearly visible, showing a good two-dimensional structure. This uniformly distributed structure indicates that there is a strong interaction between the polypeptide nanosheet and the silver sulfide quantum dots, which may be a composite material formed by electrostatic interaction, hydrogen bonding or other non-covalent interactions. The formation of this composite material is of great significance for its application in the fields of biomedicine, environmental protection and nanomaterials.
[0073] Example 3
[0074] The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods described in this embodiment includes the following steps:
[0075] Step a, weigh 2 mg of a polypeptide solid powder with a purity of 95% in a beaker, dissolve it in 2 mL of 0.1% trifluoroacetic acid / ethanol solution (ratio 1:1) under stirring to form a 1 mg / mL uniformly dispersed polypeptide solution; then place the polypeptide reaction solution in a 47°C water bath for reaction for 2-12 hours to form a polypeptide nanosheet material for standby use;
[0076] In this embodiment, the polypeptide sequence of the polypeptide solid powder is Fmoc-phenylalanine-lysine-lysine-glycine-serine-histidine. In this sequence, Fmoc is the protecting group of the N-terminus, and the other amino acids are linked together in sequence to form a polypeptide chain. Fmoc-phenylalanine is hydrophobic and aromatic, two consecutive lysines provide additional positive charge, glycine has no side chain and contributes to flexibility, serine increases hydrophilicity, and histidine has a pH-sensitive imidazole group that can adjust the charged state under pH value.
[0077] In this embodiment, sample preparation: take an appropriate amount of the polypeptide nanosheet solution obtained in step a, drop it onto a clean silicon wafer, ensure that the sample evenly covers the surface of the silicon wafer, let the sample dry naturally or blow dry with nitrogen to remove the solvent and form a stable sample layer;
[0078] Sample loading: Fix the silicon wafer with the sample on the sample stage of the atomic force microscope;
[0079] Atomic force microscope settings: Set the atomic force microscope working mode to non-contact mode or tapping mode, and adjust the scanning parameters;
[0080] Image acquisition: Start atomic force microscope scanning to obtain the three-dimensional morphology image of the polypeptide nanosheet;
[0081] Data analysis: The obtained images were analyzed using the software supporting the atomic force microscope to measure the size, thickness and other parameters of the peptide nanosheets;
[0082] Results: Figure 3 As shown, the morphology and size of the polypeptide nanofibers synthesized under the experimental conditions are shown, indicating that the nanofibers have an elongated strip structure with a length between 100-200nm and a thickness of about 4nm. This morphology indicates that polypeptide molecules can self-assemble to form an ordered nanostructure under specific conditions.
[0083] Step b, mixing the polypeptide nanosheet obtained in step a with 0.5 mL of 10 mM silver nitrate solution, reacting for 12 hours under magnetic stirring (speed 200 rpm), and then separating by dialysis (molecular weight 10,000);
[0084] Step c, dilute with water to 2 mL, then add 10 μL of sodium sulfide solution to react for 2 hours to synthesize a polypeptide sheet / silver sulfide quantum dot composite material; finally, centrifuge the obtained mixed solution (centrifugal speed of 10000 rpm, centrifugal time of 15 min) and wash 3 times, collect the final precipitate, and disperse it in 2 mL of ultrapure water.
[0085] In this embodiment, the detection process is:
[0086] Sample preparation: Take an appropriate amount of the peptide nanosheet / silver sulfide quantum dot composite material solution obtained in step c, drop it onto the copper mesh, let the sample dry naturally or use filter paper to absorb excess liquid, and ensure that a thin layer of composite material is formed on the copper mesh;
[0087] Sample loading: The copper grid with the sample was fixed on the sample holder of the transmission electron microscope;
[0088] Transmission electron microscope settings: Adjust the operating voltage of the transmission electron microscope to 100-300 kV to obtain a clear image and adjust the appropriate magnification;
[0089] Image acquisition: Start transmission electron microscope scanning to obtain a two-dimensional projection image of the polypeptide nanosheet / silver sulfide quantum dot composite material;
[0090] Data analysis: Use the transmission electron microscope software to analyze the obtained images, measure the size, distribution and other parameters of the quantum dots, analyze the electron diffraction (SAED) pattern, and confirm the crystal structure of the quantum dots;
[0091] Results: Figure 4 As shown, the microstructure of the polypeptide nanosheet / silver sulfide quantum dot composite material is shown by transmission electron microscopy (TEM). It can be seen from the figure that a large number of silver sulfide quantum dots are evenly distributed on the polypeptide nanosheet, and these quantum dots appear as dark granules, while the polypeptide nanosheet appears as a lighter background; it can be seen from the figure that the silver sulfide quantum dots are very evenly distributed on the polypeptide nanosheet, which indicates that the combination of polypeptide and silver sulfide quantum dots during the synthesis process is effective, and no obvious aggregation phenomenon occurs; the size of the silver sulfide quantum dots is small and presents a spherical or nearly spherical shape. The size of these quantum dots is within the nanoscale range, which meets the definition of quantum dots; the thickness and morphology of the polypeptide nanosheet are also clearly visible, showing a good two-dimensional structure; this uniformly distributed structure indicates that there is a strong interaction between the polypeptide nanosheet and the silver sulfide quantum dots, which may be a composite material formed by electrostatic interaction, hydrogen bonding or other non-covalent interactions; the formation of this composite material is of great significance for its application in the fields of biomedicine, environmental protection and nanomaterials.
[0092] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods, characterized in that: The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods comprises the following steps: Step a, synthesis of self-assembling polypeptide nanostructures: by customizing the amino acid sequence of polypeptide molecules and regulating the molecular self-assembly reaction conditions, a self-assembling polypeptide nanostructure is synthesized; Step b, adsorption and binding of precursor metal ions: by adjusting the pH value of the self-assembled polypeptide nanostructure solution synthesized in step a, and then adding precursor metal ions, the precursor metal ions are adsorbed and electrostatically bound to the polypeptide nanostructure to form a polypeptide nanostructure / metal ion hybrid; Step c, biomimetic synthesis of polypeptide / quantum dot composite nanomaterials: adding a reducing agent and a sulfide solution to the polypeptide nanostructure / metal ion hybrid solution synthesized in step b to prepare polypeptide / quantum dot composite nanomaterials.
2. A method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods as claimed in claim 1, characterized in that: Step a specifically includes the following steps: Step a1, weigh 5-10 mg of polypeptide sample powder in a small beaker, dissolve it in 10 mL of 0.1% trifluoroacetic acid solution under stirring to prepare a polypeptide solution with a concentration of 0.5-1 mg / mL; Step a2, reacting the polypeptide solution obtained in step a1 in a water bath at 37-57° C. for 1-3 days to synthesize a self-assembled polypeptide nanostructure, wherein the self-assembled polypeptide nanostructure comprises at least one-dimensional nanofibers and two-dimensional nanosheets.
3. The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods as claimed in claim 1, characterized in that: Step b specifically comprises the following steps: Step b1, taking 5 mL of the self-assembling polypeptide nanostructure solution synthesized in step a, adding 5 mL of the metal ion precursor solution under stirring at a speed of 200 rpm, adjusting the pH value, and reacting at room temperature for 4-6 hours; Step b2: the prepared reactants are separated by dialysis bags for standby use, wherein the molecular weight of the dialysis bags is 3000-10000.
4. The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods as claimed in claim 1, characterized in that: The precursor metal ion in step b is chloroaurate ion, silver ion or copper ion.
5. The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods as claimed in claim 1, characterized in that: In step b, the pH value of the self-assembled polypeptide nanostructure solution is adjusted according to the isoelectric point of the polypeptide.
6. The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods as claimed in claim 1, characterized in that: Step c specifically includes the following steps: Step c1, dissolving the polypeptide / metal ion product separated by dialysis in step b in 2 mL of water, and adding a reducing agent under stirring at a speed of 200 rpm to synthesize metal quantum dots; Step c2, dissolving the polypeptide / metal ion product separated by dialysis in step b in 2 mL of water, and adding the sulfide solution under stirring at a speed of 200 rpm to synthesize metal sulfide quantum dots; Step c3: removing the unreacted reducing agent and sulfide by centrifugation to synthesize the polypeptide / quantum dot composite nanomaterial.
7. A method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods as claimed in claim 6, characterized in that: The reducing agent in step c1 is sodium borohydride, and the sulfide in step c2 is sodium sulfide.
8. The method for preparing quantum dot nanomaterials using biological templates and biomimetic synthesis methods as claimed in claim 6, characterized in that: The centrifugal speed of the centrifugal operation in step c3 is 10000 rpm and the centrifugal time is 15 min.
Citation Information
Patent Citations
Polypeptide, and method for biosynthesizing near-infrared silver sulfide quantum dot
CN112175044A
Polypeptide-gold nanoparticle compound as well as preparation method and application thereof
CN114106108A
